2018
DOI: 10.1111/andr.12490
|View full text |Cite
|
Sign up to set email alerts
|

Virgin coconut oil extract mitigates testicular‐induced toxicity of alcohol use in antiretroviral therapy

Abstract: The consumption of alcohol by people living with HIV/AIDS is associated with a graver prognosis. Long-term use of antiretrovirals may have certain health challenges that may be aggravated by concomitant alcohol use. This study investigated virgin coconut oil (VCO) as an adjuvant to the deleterious effects of highly active antiretroviral therapy (HAART) and alcohol on the cyto-architecture and functioning of the testis. Forty adult male Sprague-Dawley rats, weighing 165~176 g, were divided into eight groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 67 publications
6
14
1
Order By: Relevance
“…Accumulating evidence shows that natural products have potentials to modulate undesirable side effects of anticancer drugs without altering their anticancer efficacy (Yin, Wei, Jian, & Yang, ). Natural oils such as VCO and MOO are evolving as functional foods due to their health‐promoting pharmacological activities reported in published literature (Abarikwu et al, ; Famurewa et al, ; Ogedengbe et al, ). The current study explored the antioxidant and anti‐inflammatory effects of VCO and MOO supplementation on cerebral neurotoxicity induced by MTX in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence shows that natural products have potentials to modulate undesirable side effects of anticancer drugs without altering their anticancer efficacy (Yin, Wei, Jian, & Yang, ). Natural oils such as VCO and MOO are evolving as functional foods due to their health‐promoting pharmacological activities reported in published literature (Abarikwu et al, ; Famurewa et al, ; Ogedengbe et al, ). The current study explored the antioxidant and anti‐inflammatory effects of VCO and MOO supplementation on cerebral neurotoxicity induced by MTX in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Findings here are consistent with previous reports from in vivo studies regarding MOO and VCO antioxidant actions. VCO has been suggested as a promising natural agent to mitigate drug toxicity (Famurewa et al, ; Ogedengbe et al, ). A number of in vivo systematic investigations have suggested that MOO could reverse oxidative damage to the liver and testes via increased CAT, SOD, GPx activity, and decreased MDA level (Abarikwu et al, ; Olatosin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of chronic administration of drugs that can induce toxicity when cells are dividing actively during spermatogenesis eventually leads to cessation, which also plays significant roles in germinal epithelial cell degeneration. In addition, testicular function is impaired when basement membrane is altered (Ogedengbe et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“… Group A: received distilled water as control Group B: received 100 mg/kg C. longa Group C: received 200 mg/kg C. longa Group D: received HAART‐SYMFI containing tenofovir, lamivudine and efavirenz (300, 300 and 600 mg/day respectively); 100 ml of distilled water was used to dissolve it and then adjusted to the animal equivalent dose of 0.51, 0.51 and 1.03 mg/kg body weight respectively (Ogedengbe et al., 2018). Group E: received HAART and 100 mg/kg C. longa (Shaikh et al, 2013) Group F: received HAART and 200 mg/kg C. longa (Shaikh et al, 2013) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation